Record of mega-earthquakes in subduction thrusts: The black fault rocks of Pasagshak Point (Kodiak Island, Alaska) - MENEGHINI, FRANCESCA; Di Toro, G.; Rowe, C. D.; Moore, J. C.; Tsutsumi, A.; Yamaguchi, A. (Geological Society of America Bulletin, 2010)
On Kodiak Island, Alaska, decimeter-thick black fault rocks are at the core of foliated cataclasites that are tens of meters thick. The cataclasites belong to mélange zones that are regarded as paleodécollements active at 12–14 km depth and 230–260 °C. Each black layer is mappable for tens of meters along strike. The black fault rocks feature a complex layering made at micro-scale by alternation of granular and crystalline micro textures, both composed of micron-scale sub-rounded quartz and plagioclase in an ultra-fine, phyllosilicate-rich matrix. In the crystalline micro-layers, tabular zoned microlites of plagioclase make up much of the matrix. No such feldspars have been found in the cataclasite. We interpret these crystalline micro-layers as pseudotachylytes. The granular micro-layers show higher grain-size variability, crushed microlites, and textures typical of fluidization and granular flow deformation. Crosscutting relationships between granular and crystalline micro-layers include flow and intrusion structures and mutual brittle truncation. This suggests that each decimeters-thick composite black fault rock layer records multiple pulses of seismic slip. In each pulse, ultracomminuted fluidized material and friction melt formed and deformed together in a ductile fashion. Brittle truncation by another pulse occurred after solidification of the friction melt and the fluidized rock. X-ray powder diffraction (XRPD) and X-ray fluorescence (XRF) analyses show that black fault rocks have similar mineral composition composition and chemical content as the cataclasites. The observed systematic chemical differences cannot be explained by bulk or preferential melting of any of the cataclasite components. The presence of an open, fluid infiltrated system with later alteration of black fault rocks is suggested. The geochemical results indicate that these subduction-related pseudotachylytes differ from those typically described in crystalline rocks and other tectonic settings.